STRENGTHENING BANK LIQUIDITY: ANTICIPATING POST-COVID-19 RELAXATION CESSATION WITH INSTITUTIONAL OWNERSHIP AND CAPITAL STRUCTURE - Nurmalasari, Made Ratih; Prawitasari, Putu Putri; Diah Kumalasari, Putu (International Journal of Global Accounting, Management, Education, and Entrepreneurship, 2024)
This study aims to examine the impact of institutional ownership and capital structure on banking liquidity in Indonesia in the context of the impending cessation of relaxation measures by Bank Indonesia and the Financial Services Authority (OJK) post-COVID-19 pandemic. Using data collected from several banks in Indonesia and analyzed through multiple linear regression methods, this research investigates how institutional ownership and capital structure, measured by the Debt to Equity Ratio (DER), influence bank liquidity as measured by the Current Ratio. Additionally, this study proposes new innovations for optimizing institutional ownership to enhance banking liquidity, including increased financial transparency, the adoption of blockchain technology for asset management, and the development of sustainable financial products. The analysis results show that institutional ownership has a positive and significant impact on bank liquidity, where an increase in institutional ownership contributes to enhanced liquidity. Conversely, capital structure, as measured by DER, has a negative and significant impact on bank liquidity. This indicates that an increase in DER tends to reduce bank liquidity. Based on these findings, innovative recommendations are provided for banks to optimize their institutional ownership and capital structure.